Progressive ductile shearing during till accretion within the deforming bed of a palaeo-ice stream. (1st August 2018) - Phillips, Emrys; Spagnolo, Matteo; Pilmer, Alasdair C.J.; Rea, Brice R.; Piotrowski, Jan A.; Ely, Jeremy C.; Carr, Simon
Abstract: This paper presents the results of a detailed microstructural study of a thick till formed beneath the Weichselian (Devensian) Odra palaeo-ice stream, west of Środa Wielkopolska, Poland. This SE-flowing ice stream was one of a number of corridors of faster flowing ice which drained the Scandinavian Ice Sheet in the Baltic region. Macroscopically, the massive, laterally extensive till which formed the bed of this ice stream lacks any obvious evidence of glaciotectonism (thrusting, folding). However, microscale analysis reveals that bed deformation was dominated by foliation development, recording progressive ductile shearing within a subhorizontal subglacial shear zone. Five successive generations of clast microfabric (S1 to S5) have been identified defining a set of up-ice and down-ice dipping Riedel shears, as well as a subhorizontal shear foliation coplanar to the ice-bed interface. Cross-cutting relationships between the shear fabrics record temporal changes in the style of deformation during this progressive shear event. Kinematic indicators (S-C and ECC-type fabrics) within the till indicate a consistent SE-directed shear sense, in agreement with the regional ice flow pattern. A model of bed deformation involving incremental progressive simple shear during till accretion is proposed. The relative age of this deformation was diachronous becoming progressively younger upwards, compatible with subglacial shearing having accompanied till accretion at the top of the deforming bed. Variation in the relative intensity of the microfabrics records changes in the magnitude of the cumulative strain imposed on the till and the degree of coupling between the ice and underlying bed during fast ice flow. Highlights: Detailed microstructural study of subglacial deformation beneath a palaeo-ice stream. Deformation was dominated by foliation development in response to ductile shear. Proposed model involves incremental progressive simple shear during till accretion. Variation in cumulative strain and degree of ice-bed coupling during fast ice flow.